An Atypical Porencephalic Cyst Manifesting as a Simple Partial Seizure: A Case Report and Literature Review - Abdulaziz Ibrahim Al Thafar; Abdullatif Sami Al Rashed; Bayan Abdullah Al Matar; Abdulaziz Mohammad Al-Sharydah; Abdulrahman Hamad Al-Abdulwahhab; Sari Saleh Al-Suhibani (Case Reports in Neurological Medicine)
Background. Porencephaly is an extremely rare neurological disease characterized by the presence of solitary or multiple degenerative cerebrospinal fluid (CSF) cavities within the brain parenchyma. Case Report. We describe a case involving a 23-year-old male who presented with involuntary movements of the left upper limb of 6 months’ duration. A diagnosis of porencephaly was confirmed by magnetic resonance imaging (MRI). Conclusion. The rarity of occurrence and atypical presentation of such a lesion present a challenge to clinicians. Little is known about the pathogenesis and appropriate management of porencephaly. Further studies of the implications of porencephaly for neurodevelopment and behavior are needed.